SARS-CoV-2 management in Emergency Department: risk stratification and care setting identification proposal based on first pandemic wave in Pisa University Hospital - Greta Barbieri; Alessandro Cipriano; Stella Carrara; Stefano Spinelli; Francesco Cinotti; Francesca Foltran; Matteo Filippi; Ferruccio Aquilini; Michele Tonerini; Massimo Santini; Paolo Malacarne; Lorenzo Ghiadoni (Emergency Care Journal, 2021)
SARS-CoV-2 management in Emergency Department: risk stratification and care setting identification proposal based on first pandemic wave in Pisa University Hospital